LH Levels May Be Used as an Indicator for the Time of Antagonist Administration in GnRH Antagonist Protocols—A Proof-Of-Concept Study - Liu, Minghui; Liu, Shan; Li, Lingxiu; Wang, Peng; Li, Huanhuan; Li, Yuan (Frontiers in Endocrinology, 2019)
Objective: To investigate whether circulating LH levels could be used as an indicator for the timing of antagonist addition in GnRH antagonist protocol. Design: Retrospective cohort study. Setting: University-based hospital. Patients: A total of 567 women stimulated with recombinant FSH monotherapy in a GnRH antagonist protocol were studied. Among them, 256 patients showed relatively low LH levels [highest LH level (LHmax) < 4 IU/L] during the entire ovarian stimulation process; 88 (Group A) and 168 patients (Group B) were stimulated without and with antagonist co-treatment, respectively. The remaining 311 patients had LHmax≥4 IU/L and were stimulated with a modified flexible antagonist protocol based on LH levels (Group C). Intervention(s): Patients in Group B and C received antagonist during ovarian stimulation, whereas patients in Group A did not. Main outcome measure: Clinical pregnancy rate and ongoing pregnancy rate. Results: The clinical and ongoing pregnancy rates were significantly higher in group A than group B (69.3 vs. 54.7%, P = 0.03 and 62.5 vs. 48.2%, P = 0.04, respectively), but the primary outcome measures did not differ between groups B and C. There were no significant differences in terms of patient demographics, LH levels, total dosage of gonadotrophin, duration of stimulation, follicular output rate between groups A and B, and between groups B and C. Also, there were no significant differences in laboratory and clinical outcomes in pairwise group comparisons. No canceled cycles due to premature ovulation was reported among the treated patients. Conclusion: LH levels may be used as an indicator for the time of antagonist addition. Patients with sustained low LH levels (LHmax<4 IU/L) during controlled ovarian stimulation (COS) might not require antagonist administration. Although further well-designed randomized controlled trials (RCTs) are needed to confirm our results, a novel treatment regimen based on LH measurements during COS might provide clinicians new insights about when to start antagonist administration in the GnRH antagonist protocol.